Effect of DC micro-plasma treatment on bacteria in its vegetative bacteria. Issue 1 (May 2020) - Naeem, M; Bashir, W; Altaf, N U H; Naz, M Y; Shukrullah, S; Rehman, S U; Shahid, M
Abstract: Argon gas plasma consists of discharge pattern of micro hollow cathode. The pattern is used to inactivate the two main kinds of bacteria. The Culture of Escherichia Coli (gram positive) and Staphylococcus aureus (gram negative) are subjected to the plasma exposure. The micro-plasma jet (MPJ) discharge was generated in the voltage range of 2-10 kV with an operating current of 20-35 mA. Under such conditions, a MPJ of approximately 1 cm visible length was produced. The power efficiency of this device was approximately 80%. The efficacy of MPJ to inactivate the bacteria is determined by observing colony forming unit (CFU) counts before and after plasma exposure. The Colony counter is used here to find the CFU/plate. The effect of plasma exposure is observed by varying the time at 15, 30, 60, 90, 120, 150 and 180 seconds. An efficient reduction in CFU is observed after plasma exposure, particularly for 120 seconds. Approximate 50% decay of both cultures is observed after treatment time of 120 seconds.